The Concept of Village Empowerment Based on Local Wisdom and the Creative Economy of South Tugu Village - Sudrajat, Helmalia Shinta Putri; Dewi, Yuli Sartika; Rizqy, Afrida; Anggraini, Dewi (prodima@fe.uika-bogor.ac.id, 2023)
Community empowerment refers to the ability of people to have access to productive resources that enable them to increase their income, both goods and services. This empowerment process does not appear automatically but grows and develops based on the interaction of the local community and with outsiders. This study used a qualitative research approach with an interview method which was conducted by interviewing 3 related respondents namely village heads, economic activity actors, and batik craftsmen. The author finds compatibility between village empowerment and programs that have been created through the implementation of local wisdom-based village empowerment managed by Village-Owned Enterprises (Bumdes) for the village which provides community guidance to be able to learn batik, manage UMKM and digitize promotional media that make villages more advanced and prosperous society. After conducting more intense research analysis, in the end, this village empowerment is the most important component in the progress of each village, to improve the creative economy in the village, especially Tugu Selatan Village, so that it becomes an inspiration and innovation for other villages to become prosperous villages. in terms of culture, economy, and society. The findings in this study are that Tugu Selatan Village has succeeded in empowering the community for the advancement of the village by maximizing the culture around it and utilizing it as a source of the village's economy.